The Influence Of In- Store As A Mediation To Impulse Buying (Study On The Retails In Yogyakarta) - Wisnalmawati Wisnalmawati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Impulse buying often takes place inside the store. Impulse buying describesunplanned purchasing decisions.This research aims to: 1.analyse hedonic motivethat directly affects impulse buying, 2. analyse direct marketing that directly affectsimpulse buying, 3. hedonic motive and direct marketing influence on impulsebuying mediated by in store. Subjects in this research are consumers of threeclothing stores in Yogyakarta. The sample uses as many as 75 respondents, dataanalysis technique uses Structural Equational Model (SEM) with Smart PLS 3.0Program. The results of this research prove: 1. hedonic motive has influenced onimpulse buying, 2.direct marketing has influenced on impulse buying, 3 hedonicmotive and direct marketing influence on impulse buying mediated by in store. Thefindings of this study may contribute to consumer behaviour models, at retails andTripple duties of Higher Education.Keywords: hedonic motive; direct marketing; in store; and impulse buying